The Role of Intermediary Languages in the Development of Lexical and Grammatical Features of Borrowings: Investigating Italian and Russian Languages - Tania Triberio; Erika Avakova (Translation Studies: Theory and Practice, 2024)
This study aims to contribute to the analysis of specific words entering a target language (TL) from a source one (SL), through intermediary languages (IL). In particular, this paper will analyse a selection of borrowings that entered Italian (TL) from Russian (SL) and vice-versa, focusing on the role played by IL ​​with respect to the ‘features’ the borrowing shows when entering a TL. The analysis will develop over three main phases: (i) brief excursus about theoretical studies on ‘contact linguistics’; (ii) analysis on the way a selection of both direct & indirect borrowings entered, alternatively, one of the two TLs, at different lexical and grammatical levels; (iii) a case study: the Russianism ‘boiar(d)o’ entering Italian. Some conclusions will be drawn in relation to the importance of a transversal approach, both linguistic and historical, in the analysis of interference phenomena.